Omega-3 content and sensory evaluation of scrambled eggs from two strains of laying hens fed diets enriched with alpha-linolenic acid - Kartikasari, L. R.; Geier, M. S.; Hughes, R. J.; Bastian, S. E. P.; Gibson, R. A. (Diponegoro University, 2024)
The objective of the study was to assess the accumulation of omega-3 (n-3) fats and the sensory quality of scrambled eggs from two strains of laying hens (brown and white) given omega-3 enriched diets. The design of this research was a completely randomized block design, with a 3 × 2 factorial. A total of 24 Hy-Line brown and 24 Hy-Line white were fed three experimental diets. The alphalinolenic acid (18:3n3, ALA) levels of the dietary treatments were either low (0.3%), moderate (3.0%), or high (6.0%) with the linoleic acid (18:2n6, LA) level kept constant at approximately 4%en. The results showed that dietary supplementation of ALA enhanced n-3 fats and had no impact (P>0.05) on sensory properties including oily odour, butter aroma, sulphur aroma, taste, flavour, or off-flavour of scrambled eggs. Diets high in ALA resulted in Scrambled eggs with less intense egg aroma compared to those given diets with low or moderate ALA. Eggs of brown hens had a significantly stronger egg aroma, butter flavour, and sulphur flavour (P<0.05) compared to white eggs. In conclusion, the dietary inclusion of 3.0% ALA was discovered to be optimum with respect to the accumulation of n-3 fats and the sensory properties of the eggs.